Increased P2X7 Receptor Binding Is Associated With Neuroinflammation in Acute but Not Chronic Rodent Models for Parkinson’s Disease - Crabbé, Melissa; Van der Perren, Anke; Bollaerts, Ilse; Kounelis, Savannah; Baekelandt, Veerle; Bormans, Guy; Casteels, Cindy; Moons, Lieve; Van Laere, Koen (Frontiers in Neuroscience, 2019)
The purinergic P2X7 receptor is a key mediator in (neuro)inflammation, a process that is associated with neurodegeneration and excitotoxicity in Parkinson’s disease (PD). Recently, P2X7 imaging has become possible with [11C]JNJ-(54173)717. We investigated P2X7 availability, in comparison with availability of the translocator protein (TSPO), in two well-characterized rat models of PD using in vitro autoradiography at multiple time points throughout the disease progression. Rats received either a unilateral injection with 6-hydroxydopamine (6-OHDA) in the striatum, or with recombinant adeno-associated viral vector overexpressing human A53T alpha-synuclein (α-SYN) in the substantia nigra. Transverse cryosections were incubated with [11C]JNJ-717 for P2X7 or [18F]DPA-714 for TSPO. [11C]JNJ-717 binding ratios were transiently elevated in the striatum of 6-OHDA rats at day 14-28 post-injection, with peak P2X7 binding at day 14. This largely coincided with the time course of striatal [18F]DPA-714 binding which was elevated at day 7-21, with peak TSPO binding at day 7. Increased P2X7 availability co-localized with microglial, but not astrocyte or neuronal markers. In the chronic α-SYN model, no significant differences were found in P2X7 binding, although in vitro TSPO overexpression was reported previously. This first study showed an increased P2X7 availability in the acute PD model in a time window corresponding with elevated TSPO binding and motor behavior changes. In contrast, the dynamics of TSPO and P2X7 were divergent in the chronic α-SYN model where no P2X7 changes were detectable. Overall, extended P2X7 phenotyping is warranted prior to implementation of P2X7 imaging for monitoring of neuroinflammation.